A ferramenta virtual Vocaroo como recurso pedagógico no ensino de língua portuguesa na modalidade oral - Gabi, Wuilians Jonys Tavares (2022)
The present research aimed to present the virtual tool vocaroo as a pedagogical support for the teaching of Portuguese Language in oral modality, in the elementary school. First, we address the manifestation of orality in the field of linguistics and according to official documents, based on Carvalho and Ferrarezi Junior (2017), Marcuschi (2001), Marcuschi (2010), Heine (2012), Flannery (2015), Lessa and Rodrigues (2010), Schneuwly (2004), PCN (1997) and BNCC (2017). Then, we also reflect on Digital Literacy based on Street (2004), Rojo and Moura (2019), Soares (2002) and Kleiman (1995) and on the role of the school in this context according to Moran (2013) and Coscarelli (2016). We bring the Virtual Tools not Exclusive to Learning - FVNexA (MATOS, 2020). In this sense, the virtual tool vocaroo is observed, within its possibilities, as ItemNet (MATOS, 2020) susceptible to the intervention of the agent (teacher). As for the methodology, the research involved the development and application of a didactic sequence based on Dolz Noverraz e Schneully 's (2004) model using the vocaroo tool for teaching Portuguese to 7th grade students in a public school. The results show that the vocaroo tool is an excellent support for teaching the linguistic content "punctuation", besides providing the students' digital literacy. We also concluded that the vocaroo tool was able to transform itself into a FVNexA, through the performance of the teaching agent.